Advancements in optical methods and digital image correlation in experimental mechanics. Advancements in optical methods and digital image correlation in experimental mechanics. Volume 3, Proceedings of the 2019 Annual Conference on Experimental and Applied Mechanics. / Volume 3, ([2020]) - Unknown
No abstract available